Healthcare experiences of LGBTQ+ people: non-binary people remain unaffirmed - Nowaskie, Dustin Z.; Menez, Olwen (Frontiers in Sociology, 2024)
IntroductionLesbian, gay, bisexual, transgender, queer, and all sexually and gender diverse (LGBTQ+) people experience discrimination across many contexts, including healthcare environments. While some research has shown transgender people and non-binary people often endure higher rates of marginalization than cisgender, sexually diverse people, past data are limited.MethodsA sample of LGBTQ+ people (N = 173) in the United States completed an anonymous, online, self-reported survey, which included the Consumer Assessment of Healthcare Providers and Systems and healthcare experience questions. Groups, including people who identified as cisgender, sexually diverse (n = 116), transgender (n = 24), and non-binary (n = 33), were compared using chi-square and multivariate analysis of covariance tests.ResultsCompared to cisgender, sexually diverse people, non-binary people were less likely to report feeling comfortable with a physical exam, having good mental health, respected by providers, that providers had adequate medical information, that providers could care for someone going through gender affirmation, and that hospital staff were comfortable interacting with them. Additionally, non-binary people were more likely to report hospital staff misgendering them.DiscussionThese unique LGBTQ+ subgroup differences may be secondary to identity-specific stigma that non-binary people face. More international studies are needed to elucidate these subgroup-specific healthcare experiences across LGBTQ+ identities.